Take My Word for It - Safire, William (Lahore Combine Printers (Pvt.) Ltd., 1987)
Includes material on slang, jargon, neologisms, and readers' letters.
Include Index.
Keywords: English language--Errors of usage -- English language--Etymology -- English language--Usage